THE INFLUENCE OF ORGANIZATIONAL CREATIVITY AND ORGANIZATIONAL INNOVATION ON ORGANIZATIONAL PERFORMANCE IN PT. NUSANTARA PLANTATIONS IV REGIONAL I MEDAN - Isma Nanda Saputri; Hery Syahrial; Tohap Parulian Sihombing (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to determine the effect of organizational creativity and organizational innovation on organizational performance at PT. Perkebunan Nusantara IV Regional I Medan partially. This study uses a quantitative approach with a sample of 165 employees selected using stratified proportional sampling and convenience sampling. Data were distributed to respondents using a questionnaire with a Likert scale of 1-5 which was distributed directly and also via google form. Furthermore, the data obtained were analyzed using multiple linear regression with SPSS software version 23. The results of the analysis showed a positive and significant effect between organizational creativity on organizational performance, as well as a positive and significant effect between organizational innovation on organizational performance. This study contributes to the integration of organizational creativity and organizational innovation on organizational performance in one research framework, which in previous studies to the best of the researcher's knowledge has not been found, and also enriches the literature review related to antecedents of organizational performance in the context of plantation sector research. Furthermore, this study provides input to leaders about the importance of organizational creativity and organizational innovation in improving organizational performance.